2010
DOI: 10.1590/s0100-40422010000200025
|View full text |Cite
|
Sign up to set email alerts
|

Método extendido de Hildebrand en la predicción de la solubilidad del ketoprofeno en mezclas cosolventes etanol + agua

Abstract: Recebido em 1/4/09; aceito em 24/7/09; publicado na web em 11/1/10 INTRODUCCIÓNEl ketoprofeno (KTP) es un derivado del ácido propiónico y farmacológicamente tiene acción analgésica y está clasificado como anti-inflamatorio no esteroidal (AINE). Por sus propiedades es ampliamente utilizado en la terapéutica actual para el tratamiento de diversos procesos agudos o crónicos relacionados con dolor e inflamación. 1De otro lado, es bien sabido que las formulaciones líquidas inyectables se caracterizan por suministr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…& Roseman, T.J. (1981) was also challenged in front to the experimental solubility values at equilibrium of this drug. Thus, this investigation expands the information reported previously for the solubility estimation of naproxen and ketoprofen in the same cosolvent system (Vargas, E. et al 2008;Gantiva, M. et al 2009).…”
Section: Introductionsupporting
confidence: 84%
“…& Roseman, T.J. (1981) was also challenged in front to the experimental solubility values at equilibrium of this drug. Thus, this investigation expands the information reported previously for the solubility estimation of naproxen and ketoprofen in the same cosolvent system (Vargas, E. et al 2008;Gantiva, M. et al 2009).…”
Section: Introductionsupporting
confidence: 84%
“…Physicians prescribe ketoprofen to individuals suffering with osteoarthritis and rheumatoid arthritis to manage pain and inflammation. There have been several published studies 60,64,65,100,[131][132][133][134][135][136][137][138][139][140][141][142][143] involving the solubility of ketoprofen in organic solvents at 298 K. Most notably, Perlovich et al 136 determined the molefraction solubility of ketoprofen in eight primary alcohols (methanol, ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, and 1-octanol). Daniels et al 134 later reported the solubility behavior of ketoprofen in ethyl ethanoate, 1,1′-oxybisethane, methanol, ethanol, 1-propanol, 2-propanol, 2-methyl-1-propanol, 1-pentanol, and 1-decanol.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
“…Daniels et al 134 later reported the solubility behavior of ketoprofen in ethyl ethanoate, 1,1′-oxybisethane, methanol, ethanol, 1-propanol, 2-propanol, 2-methyl-1-propanol, 1-pentanol, and 1-decanol. Bustamante and Selles, 133 Gantiva and Martínez, 139 Ribeiro et al, 137 and Fini et al 60 also performed ketoprofen solubility measurements at 298 K. Takahashi et al 100 measured the solubility of ketoprofen in diethyl butanedioate, diethyl hexanedioate, diisopropyl hexanedioate, and diethyl decanedioate at 305 K in their study concerning the use of fatty diesters as a means to enhance NSAID permeation through skin. Wenkers and Lippold 64 reported solubility data for ten NSAIDs (aspirin, diclofenac, diflunisal, flufenamic acid, ibuprofen, ketoprofen, nabumetone, naproxen, piroxicam, and tenoxicam) in light mineral oil at 305 K. Kumprakob et al 141 determined the solubility of ketoprofen in binary water + 1,2-propanediol and water + 1,2,3-propanetriol solvent mixtures at 310 K over the entire solvent composition range.…”
Section: Critical Evaluation Of Experimental Solubility Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, Park et al [35] used HSPs as necessary data to calculate the equilibrium solubility of ascorbic acid, citric acid, butylated hydroxytoluene (BHT), caffeic acid, epicatechin, and epigallocatechin gallate in several organic functional solvents. However, they did not consider a solvent mixture evaluation in their studies as Gantiva et al [36] did to predict the solubility of naproxen in ethanol-water mixtures. Martínez [37] evaluated the solubility of acetaminophen in propylene glycol and water mixtures.…”
Section: Group Contribution Methodsmentioning
confidence: 99%